2020
DOI: 10.1002/cam4.3296
|View full text |Cite
|
Sign up to set email alerts
|

The artificial intelligence‐assisted cytology diagnostic system in large‐scale cervical cancer screening: A population‐based cohort study of 0.7 million women

Abstract: Background Adequate cytology is limited by insufficient cytologists in a large‐scale cervical cancer screening. We aimed to develop an artificial intelligence (AI)‐assisted cytology system in cervical cancer screening program. Methods We conducted a perspective cohort study within a population‐based cervical cancer screening program for 0.7 million women, using a validated AI‐assisted cytology system. For comparison, cytologists examined all slides classified by AI as abnormal and a randomly selected 10% of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 35 publications
2
40
0
1
Order By: Relevance
“…Without going into too many details, which are published elsewhere [21], our study showed high agreement rate for normal cytology grade between AI and manual reading. We showed that well-"trained AI system" can accurately classify normal cytology.…”
Section: The Start Of Ai and Cloud Computing In Cervical Cancer Screening Hubei Province Chinasupporting
confidence: 57%
“…Without going into too many details, which are published elsewhere [21], our study showed high agreement rate for normal cytology grade between AI and manual reading. We showed that well-"trained AI system" can accurately classify normal cytology.…”
Section: The Start Of Ai and Cloud Computing In Cervical Cancer Screening Hubei Province Chinasupporting
confidence: 57%
“…This technique relies on deep learning algorithms that have been developed in order to deal with a large amount data, to segment cytoplasm, and detect cervical dysplasia [ 72 ]. Even though cytological readings assisted by artificial intelligence have been shown to have similar accuracy as cytological analyses performed by capable cytologists, they are still in the early stages and require further investigation before they can be reliably used in screening programs [ 72 , 76 ]. Similarly, with DNA methylation and biomarker detection, large-scale and long-term prospective studies are required to clarify their role in screening for cervical cancer.…”
Section: Emerging Diagnostic Methodsmentioning
confidence: 99%
“…In recent years, with the rapid development of science and technology, the application of artificial intelligence (AI) based products is booming. In cervical cancer prevention and control, AI also showed to be promising in cytology-based screening and colposcopy examination based on the image pattern recognition ( 59 , 60 ). These AI-based technology or system can intelligently identify lesions and assist medical staff in clinical examination and diagnosis which could alleviate difficulties in diagnosis in primary clinics.…”
Section: Cervical Cancer Screeningmentioning
confidence: 99%